АДАПТИВНІ СПОСТЕРІГАЧІ ЧАСТОТИ ДВОФАЗНИХ ТА ОДНОФАЗНИХ ГАРМОНІЧНИХ СИГНАЛІВ - Пересада, С.М.; Ніконенко, Є.О.; Ковбаса, С.М.; Кузнєцов, О. (Інститут електродинаміки НАН України, Київ, 2023)
An adaptive observer for frequency and magnitude of two-phase symmetrical sinusoidal signal is presented. It is designed based on control concept of internal model approach. The observer guarantees global exponential estimation and high performance. If the information about one of the two-phase signal components is missing, a modified structure of the observer is proposed. This case is equivalent to the measurement of a single-phase sinusoidal signal. The properties of local exponential stability of single-phase signal observer are proved using Lyapunov’s conversion theorem for disturbed systems. The robustness of the two-phase signal observer with respect to additive disturbances (high-frequency noise, varying frequency) is confirmed by simulation results. It is shown that the observer estimation speed can be arbitrarily increased by increasing the feedback gains. A method for single-phase harmonic signal frequency observer tuning is developed, which ensures the expansion of the stability region. References 14, figures 7.